Rural households saving status and its determinant factors: Insight from southwest region of Ethiopia - Kindineh Sisay (Cogent Economics & Finance, 2023)
Especially for developing countries like Ethiopia, saving is more significant to build capital required to generate income, smooth domestic cash requirements, and allow the ease of consumption during scarcity. However, rural saving at the household level was not substantially investigated in Ethiopia in general and in the study area in particular. The current study, therefore, assessed rural households' saving status and its determinant factors in Gimbo district, south west region of Ethiopia. Out of the entire sample households surveyed, more than half (52.35%) of the surveyed households were non-saver. This is to mean that a lesser proportion of the sampled households were saving their income left from food and non-food spending or other expenses at formal financial institutions. When we look at the intensity of saving, the whole sampled households saved 4,788.15 ETB on average. As both logit and multiple linear regression model results showed, the education level of the household head, distance from financial institutions, farm income, financial literacy, and participation in non-farm activities were found to affect both decision to save and intensity of saving significantly and positively except distance from financial institutions, which is negatively correlated with both. Therefore, to overcome negative effects of distance from financial institutions, the study recommend the expansion of financial institutions up to kebele levels as much as possible. Moreover, policymakers and other concerned bodies responsible for the enhancement of rural private saving should have to amend rural households' farm income, education, financial literacy, and participation in non-farm activities.
Keywords: 330; decision to save; intensity of saving; logit; multiple linear regression; saving